Influence of serum progesterone levels on the inflammatory response of female dogs with visceral leishmaniosis - Bertolo, Paulo Henrique Leal [UNESP]; Moutinho da Conceição, Maria Eduarda Bastos Andrade [UNESP]; Emboaba da Costa, Rafael Rocha Mello [UNESP]; Jacintho, Ana Paula Prudente [UNESP]; Cipriano, Rafael Silva; Moreira, Pamela Rodrigues Reina; Ferreira, Maricy Apparício [UNESP]; Machado, Gisele Fabrino [UNESP]; de Oliveira Vasconcelos, Rosemeri [UNESP] (Elsevier, 2022)
The aim of this study was to evaluate the histopathological changes to the mammary gland that occur in female dogs with visceral leishmaniosis and to correlate the findings with the parasite load, inflammatory cell profile in mammary tissue and serum progesterone levels. For this, 20 adult female dogs that were naturally infected with Leishmania infantum, not spayed, not pregnant and free from mammary tumors were used. They were divided into two groups: G1 (n = 9) with high serum progesterone levels and G2 (n = 11) with low serum progesterone levels. The parasite load and the immunophenotype of leukocytes infiltrated into the mammary tissue (CD3, CD4, CD8 and MCA874) were evaluated using the immunohistochemical technique. In the mammary gland, chronic inflammatory infiltrate was mainly found in G1, sometimes associated with granulomatous inflammation, higher parasite load and higher density of cells immunolabeled for CD3, CD4, CD8 and MCA874. A significant positive correlation (p < 0.05) was observed between the parasite load and the immunolabeled leukocytes. The influence of the serum progesterone level in the mammary gland of infected female dogs can contribute to the maintenance of an immunosuppressive cell profile and favor the persistence of the parasite in this site.
Keywords: Dog; Hormonal influence; Immune response; Leishmania infantum; Mammary gland; Progesterone